2012
DOI: 10.3758/s13421-012-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

Top-down constraint on recognition memory

Abstract: Can recognition memory be constrained "at the front end," such that people are more likely to retrieve information about studying a recognition-test probe from a specified target source than they are to retrieve such information about a probe from a nontarget source? We adapted a procedure developed by Jacoby, Shimizu, Daniels, and Rhodes (Psychonomic Bulletin & Review 12:852-857, 2005) to address this question. Experiment 1 yielded evidence of sourceconstrained retrieval, but that pattern was not significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…If such a “source-constrained retrieval” is indeed occurring, then the “memory-for-foils” effect should be apparent following any number of different encoding manipulations (not just a level of processing one), as long as those modes of processing can be reinstated at the time of retrieval. There have been a number of corroborating studies since 2005, confirming and extending the memory-for-foils paradigm [ 12 , 13 , 14 , 15 ] and providing evidence consistent with the reinstatement of encoding processes at the time of retrieval. Importantly, Danckert, MacLeod, and Fernandes [ 2 ] showed that another encoding manipulation—other than the standard levels-of-processing manipulation—also produced the memory-for-foils pattern.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…If such a “source-constrained retrieval” is indeed occurring, then the “memory-for-foils” effect should be apparent following any number of different encoding manipulations (not just a level of processing one), as long as those modes of processing can be reinstated at the time of retrieval. There have been a number of corroborating studies since 2005, confirming and extending the memory-for-foils paradigm [ 12 , 13 , 14 , 15 ] and providing evidence consistent with the reinstatement of encoding processes at the time of retrieval. Importantly, Danckert, MacLeod, and Fernandes [ 2 ] showed that another encoding manipulation—other than the standard levels-of-processing manipulation—also produced the memory-for-foils pattern.…”
Section: Introductionmentioning
confidence: 82%
“…In fact, there were no differences between the groups until Anxiety Group and Foil Valence were taken into consideration. Unlike many other studies exploring constrained memory search [ 2 , 12 , 13 , 14 , 15 ], our study implemented an emotional context manipulation in conjunction with a depth of processing instruction at the time of encoding. The discrepancy between the findings in our study and those of prior works suggests that the inclusion of an emotional context at encoding altered the eventual downstream memory bias, reducing any effect from depth of processing alone.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we used the excellent temporal resolution of EEG to examine the temporal dynamics of the encoding of foils to obtain a better understanding of when reimplementation processes occur. It has previously been suggested that the foil effect can be explained by source constrained retrieval processes that reimplement encoding processes in the early stage of a memory test trial to guide memory search as a form of “front-end control” (Kantner & Lindsay, 2013 ; Jacoby, Shimizu, Daniels, et al, 2005 ), predicting that the neural activity associated with such reimplementation should be apparent shortly after a recognition cue is presented. An alternative, though not mutually exclusive, proposal is that control processes may be engaged at a later stage of processing, for example, to monitor whether retrieved information is correct (Halamish et al, 2012 ; Jacoby et al, 1999 ) or to elicit recollection if initial unconstrained retrieval attempts are unsuccessful as a “late correction” or “back-end control” strategy (Jacoby et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because semantic encoding typically leads to more accurate memory compared with nonsemantic encoding, this “foil effect” implies that participants strategically orient their retrieval toward a semantic processing mode when attempting to retrieve semantic encoded information and a nonsemantic processing mode when retrieving nonsemantic information, resulting in better incidental encoding of semantic compared with nonsemantic foils. Jacoby and colleagues interpreted this foil finding in light of the transfer appropriate processing principle by emphasizing the importance of the overlap in study–test operations for optimizing retrieval success (see also Zawadzka, Hanczakowski, & Wilding, 2017 ; Gray & Gallo, 2015 ; Kantner & Lindsay, 2013 ; Alban & Kelley, 2012 ; Halamish, Goldsmith, & Jacoby, 2012 ; Danckert, MacLeod, & Fernandes, 2011 ; Marsh et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…For present purposes the point is merely that it would be interesting to know more about source-constrained recall and how it interacts with SM processes that unfold as thoughts and images come to mind. (For ideas about source-constraint in recognition, see Alban & Kelley, 2012;Jacoby, Shimizu, Daniels, & Rhodes, 2005;Kantner & Lindsay, 2013. ) Marcia Johnson situates ideas about SM in the broader context of her multiple-entry modular memory (MEM) theory.…”
Section: Future Directionsmentioning
confidence: 99%